NUMERICAL STUDY ON DRAG COEFFICIENT AND EVALUATION OF THE FLOW PATTERNS IN PERFORATED PARTICLES - Afshari, Faraz; Sahin, Bayram; Marchetti, Barbara; Polonara, Fabio; Corvaro, Francesco; Leporini, Mariella; Afshari, Farzad (BEGELL HOUSE INC, 2021)
The flow regime around different shapes and surfaces has been deeply studied with numerical and experimental methods, whereas perforated particles have taken little attention among investigations. In this study, the drag coefficient and flow wake structure of spherical particles with different hole numbers and hole diameters are investigated numerically using computational fluid dynamics (CFD). In addition, the different hole numbers and sizes in the spherical model are analyzed within a wide range of Reynolds numbers. From the analysis performed it was shown that for the case when the hole number is 15 at the Re number equal to 20, the drag coefficient increases by about 0.65%, 3.76%, and 17%, when the dimensionless hole diameter is 0.02, 0.05, and 0.1, respectively. Velocity and pressure contours, streamlines, and drag coefficient histograms are discussed and compared under different flow conditions. The ANSYS Fluent 16 software is used for fluid flow analysis around and through the models mentioned.
Keywords: drag coefficient; computational fluid dynamics; 3D simulation; sphere; numerical method; SOLAR AIR HEATERS; SETTLING VELOCITY; REYNOLDS; APPROXIMATION; ENHANCEMENT; SIMULATION; MOTION; FORCE; Thermodynamics